New syllabus mathematics Workbook 3 Think! - Shazia Asad (Karachi: Oxford university press, 2024)
Key Features Questions that connect ideas within mathematics and between mathematics and the science through applications of mathematics are included to allow you to better appreciate mathematics. Challenging questions require you to apply thinking, reasoning and metacognitive skills. Open-ended questions reinforce comprehension and encourage reflection through the construction and analysis of possible answers. A Mid-year Checkpoint or an End-of-year Checkpoint consolidates the concepts covered in the textbooks and is useful for assessing your learning and identifying areas that require further practice.
Keywords: Mathematics